Konseling Individu Dengan Teknik (Rebt) Dalam Mengatasi Kecemasan Berkomunikasi Umum Pada Remaja - Erisma, Kalara; Suryati, Suryati; Jannati, Zhila (CV. ITTC INDONESIA, 2023)
Anxiety in communicating in public is a condition in which individuals feel unsafe or unpleasant, followed by physical and psychological reactions due to fears of not being able to adapt or deal with situations when speaking in public that arise before or during public speaking. in public. The purpose of this study is to determine the description of anxiety in communicating in public in adolescents before individual counseling is applied, to determine the implementation of individual counseling in the anxiety of communicating in public among adolescents, and to determine the description of anxiety in communicating in public in adolescents after counseling. individual. This research approach is a qualitative approach with descriptive research methods. The subjects of the study were 3 teenagers. Data collection techniques were observation, interviews, documentation. Data analysis techniques, the Miller and Huberman models, collected data, presented data, and reduced data. The results of this study indicate that the physiological aspects of anxiety in communicating in public in adolescents are shaking, palms are sweaty, heart rate is beating faster, regarding psychological aspects it is difficult to express words when speaking, difficulties in conveying messages smoothly, and from a behavioral aspect namely walking around the room, unable to sit for a long time. The implementation of counseling is carried out in three stages, namely the initial stage, the middle stage, the final stage, counseling is given 6x meetings, showing changes in reducing anxiety when speaking in public, the client is able to overcome situations that make him anxious and can be relieved by suggesting himself everything will be fine. fine.